Novel optical fibre dosimeters and their applications in radiotherapy: A Monte Carlo study. (October 2017) - Alharbi, Majed; Martyn, Michael; Woulfe, Peter; Chen, Lingxia; O'Keeffe, Sinead; Foley, Mark
Abstract : Monte Carlo (MC) techniques have become an essential dosimetry tool in radiotherapy. A MC model of an Elekta Agility treatment head (Elekta AB, Stockholm, Sweden) was developed. The MC software packages BEAMnrc and DOSXYZnrc were used to perform radiation transport simulations. The treatment head model consisted of several components including: the x-ray target, primary collimator, flattening filter, tongue-and-groove multi-leaf collimator, and jaws. Treatment head specifications were provided by Elekta. Accurate modelling was achieved through an iterative tuning process varying the energy and full width half maximum (FWHM) of the incident electron beam in steps of 0.1 MeV and 0.05 cm, respectively, until MC and measured lateral dose profiles and percentage depth dose curves (PDDs) agreed within 2%. Dose was scored in a user-defined homogeneous water phantom. The tuned MC model of the treatment head is then used to quantify the accuracy of our novel optical fibers. Optical fibre sensors offer several advantages over conventional dosimeters. Optical fibers have small dimensions, are immune to electromagnetic fields and can be used to remotely monitor radiation in real time. Results have been obtained using novel silica optical fibre (SOF) based and plastic optical fibre (POF) based sensors for clinical in-vivo dosimetry showing that both sensors exhibit an energy dependency. Ongoing work will include measurements using new scintillation materials, with a value for Zeff closer to that of water, which has a low dependence on radiation source energy, and benchmarking these measurements against the developed MC model and Gafchromic films.